Refleksi Pelayanan Yesus dalam Matius 14:13-21 Melalui Program-program di Pusat Pengembangan Anak - Sutrisno, Ribut Agung; Prastawa, Singgih (Sekolah Tinggi Teologi Intheos Surakarta, 2024)
Abstract. This study aimed to describe the role of the Child Development Center (PPA) as a reflection of Jesus' ministry as recorded in the Gospel of Matthew 14:13-21. This study was motivated by the decreasing participation of children in PPA programs, which ultimately has implications for the spiritual aspects of children. The method in this study is descriptive qualitative. The subjects were adolescent students at PPA IO 0933